Exploring the value proposition for RRI in Australia. Issue 3 (2nd September 2019) - Ashworth, Peta; Lacey, Justine; Sehic, Semso; Dowd, Anne-Maree
ABSTRACT: Until recently, 'Responsible Research and Innovation (RRI)' was very much a nascent concept in Australia. This research, examining RRI in the Australian context, created both expectations and scepticism about the value it might bring to Australia. Such responses are not surprising as many Australian research institutions are under increasing pressure from stakeholders to improve the performance, effectiveness, and accountability of their research. A series of interviews revealed that ' research integrity ' and ' innovation ' are considered central to Australia's research agenda. However, while exploring the meaning of RRI, different notions of ' responsibility ' emerged. Such differences appear to be influenced by the organisation type within the context of Australia's innovation system and the individual's position within that organisation. With the Australian government now focusing on impact, whether RRI becomes an accepted 'practice' will be contingent on the value it can return. Through this lens we explore conceptualisations of RRI in the Australian context.